2021
DOI: 10.21037/tau-21-758
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous, simultaneous or intravesical recurrence bladder cancer on prognosis of upper tract urothelial carcinoma after nephroureterectomy: a large population-based study

Abstract: Background: Currently, the impact of previous, simultaneous, or subsequent bladder cancer on the prognosis of upper urinary tract urothelial carcinoma (UTUC) is controversial. We aimed to investigate the impact of previous, simultaneous or intravesical recurrence (IVR) bladder cancer on the prognosis of UTUC based on a large population-based cohort from the Surveillance, Epidemiology, and End Results (SEER) database.Methods: A total of 8,431 UTUC patients diagnosed from 2004 to 2018 met the inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The overall survival was short in patients with previous or concomitant bladder cancer [ 11 ]. Zeng et al focused on cancer-specific survival and found that, after adjustment for covariates, previous or concomitant bladder cancer might have a trend of shortened CSS, although the hazard ratio is small [ 15 ]. These findings are different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival was short in patients with previous or concomitant bladder cancer [ 11 ]. Zeng et al focused on cancer-specific survival and found that, after adjustment for covariates, previous or concomitant bladder cancer might have a trend of shortened CSS, although the hazard ratio is small [ 15 ]. These findings are different from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) the primary tumor was identified by the International Classification of Diseases-O-3 (ICD-O-3) codes C64.9, C65.9. (2) the initial primary tumor was confirmed to be renal pelvis or ureter carcinoma, and (3) the histology was microscopically confirmed. Patients were excluded if distant metastasis, survival months, and vital status were unknown, or the tumor was a secondary lesion.…”
Section: Study Populationmentioning
confidence: 99%
“…upper tract urothelial carcinoma (UTUC) is a rare and highly malignant tumor, affecting only 2 in 100,000 people (1). Although the incidence of UTUC has continued to increase, with the greater use of cross-sectional imaging, UTUC only accounts for 5%-10% of urothelial carcinoma (2,3). In this population, the incidence of metastatic UTUC is even lower, estimated to be only 12%-16% at the time of initial diagnosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited evidence to support the role of history of previous malignancy (HPM), especially the history of non-urothelial cancers. According to several publications, a history of bladder cancer before UTUC could significantly increase the rate of intravesical recurrence (IVR) [ 3 , 4 ]. EAU guidelines on UTUC also set previous bladder cancer as a predictor of increased risk for bladder recurrence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%